Effect of VEGF on Angiogenesis in Pedicle Penile Skin Flaps: An Experimental Study of Urethral Reconstruction in Rabbits - Efstathiou, Elefteria; Gardikis, Stefanos; Giatromanolaki, Alexandra; Kambouri, Katerina; Sivridis, Efthimios; Simopoulos, Constantinos; Vaos, George (European Journal of Pediatric Surgery, 2012)
Introduction The aim of this study was to investigate the expression of vascular endothelial growth factor (VEGF) in pedicle penile skin flaps (PPSFs) used for urethral reconstruction in rabbits and the effect of exogenous VEGF on the angiogenesis process in the PPSFs.Methods We randomly divided 28 male New Zealand rabbits into two sets of animals. A ventral urethral defect was created in all animals. In the first set of animals (first experiment, n = 10), a PPSF was used for the repair and VEGF expression in the flap was estimated on days 1, 2, 3, 5, and 7 postoperatively. The second set of animals (second experiment, n = 18) included three groups: control, untreated, and VEGF groups. In control group (n = 6), the defect was repaired by simple closure. In untreated (n = 6) and VEGF (n = 6) groups, a PPSF was used for the reconstruction. In VEGF group, exogenous VEGF was injected subdermally on the postoperative day corresponding to the peak endogenous VEGF expression (first experiment results). The animals were sacrificed on the 21st postoperative day and the angiogenic activity was assessed. A p < 0.05 was considered statistically significant.Results The highest expression of endogenous VEGF in PPSFs was noted on postoperative day 3. Angiogenesis in control, untreated, and VEGF groups was 23.06 ± 4.1, 30.00 ± 6.9, and 34.7 ± 6.9 (mean values ± standard deviation) vessels per optical field, respectively. There were statistically significant differences between control–untreated groups (p = 0.04) and untreated–VEGF groups (p < 0.0001), and indicative difference between untreated and VEGF groups (p = 0.064).Conclusions VEGF is expressed in PPSFs, used for urethral reconstruction in rabbits. Flap angiogenesis is much higher than angiogenesis in simple wound closure. VEGF injection on postoperative day 3 seems to enhance angiogenesis in flaps.
Keywords: angiogenesis; pedicle penile skin flap; rabbit; urethral reconstruction; vascular endothelial growth factor